2011
DOI: 10.1016/j.ajpath.2011.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ischemic Tolerance Protects the Retina From Diabetic Retinopathy

Abstract: Diabetic retinopathy is a leading cause of acquired blindness. Available treatments are not very effective. We investigated the effect of a weekly application of retinal ischemia pulses (ischemic conditioning) on retinal damage induced by experimental diabetes. Diabetes was induced by an intraperitoneal injection of streptozotocin. Retinal ischemia was induced by increasing intraocular pressure to 120 mmHg for 5 minutes; this maneuver started 3 days after streptozotocin injection and was weekly repeated in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…For acute retinal ischemic injury, postconditioning with brief ischemia or carbon monoxide has proven efficacious [31][32][33][34], as has environmental enrichment [35]. Studies of postconditioning for more chronic retinal injury paradigms, however, are very limited [36,37].That repetitive postconditioning might provide a viable treatment strategy for glaucoma is supported by two preclinical studies to date. One is our previous study showing RGC soma and axon protection in the same inducible mouse model of glaucoma by intermittent hypoxic preconditioning before disease onset [9].…”
Section: Discussionmentioning
confidence: 74%
“…For acute retinal ischemic injury, postconditioning with brief ischemia or carbon monoxide has proven efficacious [31][32][33][34], as has environmental enrichment [35]. Studies of postconditioning for more chronic retinal injury paradigms, however, are very limited [36,37].That repetitive postconditioning might provide a viable treatment strategy for glaucoma is supported by two preclinical studies to date. One is our previous study showing RGC soma and axon protection in the same inducible mouse model of glaucoma by intermittent hypoxic preconditioning before disease onset [9].…”
Section: Discussionmentioning
confidence: 74%
“…Evan's blue has been widely used for BRB integrity studies [34], [35]. As previously described [20], in the retina from SE-housed diabetic animals, extravasated Evan's blue was observed, whereas EE-housing protected the BRB integrity. Since a reduction of GFAP-expression in retinal astrocytes and an increase in Müller cell GFAP levels during diabetes were linked to a reduced ability to maintain BRB integrity [31], [32], it seems likely that changes in GFAP-immunoreactivity in Müller cells and astrocytes could be involved in Evan's blue leakage in eyes from SE-housed diabetic rats, and for the preservation of BRB integrity induced by EE.…”
Section: Discussionmentioning
confidence: 97%
“…An immunohistochemical detection was performed using the LSAB2 System-HRP (Dako, California, USA), based on biotin-streptavidin-peroxidase, and visualized using 3,3′-diaminobenzidine (DAB) as chromogen, as described [20]. For immunodetection of BDNF, paraffin sections were incubated overnight at 4°C with a rabbit policlonal anti-BDNF antibody (1∶50; Santa Cruz Biotechnology, Buenos Aires, Argentina), and then, an anti-rabbit secondary antibody conjugated to Alexa Fluor 568 (1∶500; Molecular Probes, OR, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Since this original work, preconditioning has been identified in the brain, kidney, liver and the retina. In the retina, preconditioning stimuli have been shown to protect the retina from acute light, ischemic injury, as well as chronic ocular hypertensive and diabetic stress (Fernandez et al, 2011; Grimm et al, 2002; Li et al, 2003; Roth et al, 1998; Zhu et al, 2012). Initial studies described the protective periods induced by preconditioning as transient (i.e., hours to days); however, recent studies in the brain and the retina have shown that periods of protection can be extended up to four weeks using repetitive hypoxic stimuli (Stowe et al, 2011; Zhu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%